Elaboración de una compota a partir de mashua blanca (Tropaeolum tuberosum) y camote morado (Ipomoea batatas) utilizando dos tipos de endulzantes (miel de abeja y panela) a tres concentraciones - Rodríguez Zapata, Darwin Patricio (2013)
The investigation has it carried out in, Goteras 5 De Junio Neighborhood, Tanicuchi Parish, and Latacunga Canton. The surveys were realized in the C.I. B.V. ESTRELLITAS DEL FUTURO. It is located in Tanicuchi Parish, and Cotopaxi Technical University was the Experimentation and Production Centering Salache Town (CEYPSA). It belongs Agro-industrial Engineering Career. An experimental design was developed in the compotes production with an arrangement factorial AxB; factor. It corresponds to combinations of white mashua and purple yam; (a1) = 25 %, 75 %; (a2) = 50 %, 50 %; (a3) = 75 %, 25 %; the factor B corresponding to combinations of honey and panela; (b1) = 75 %, 25 %; (b2) = 50 %, 50 %; (b3) = 25 %, 75 %. After the taste, we selected the three best treatments. They are: (T9). A3b3, (T6) a2b3.75 %; (T7) a3b1. For this, they were surrendered to different types of analysis as physicist - chemist, microbiological. They were realized in the LACONAL Lab in Ambato City. The microbiological results were….